1978
DOI: 10.1139/m78-066
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Streptomyces coelicolor A3(2) aerial spore rodlet mosaic

Abstract: Cytochemical analysis of Streptomyces coelicolor (A3(2) indicated that the aerial growth rodlet mosaic is a polysaccharide. Statistical analysis of frequency distributions of individual rodlet lengths from control and ether-reoriented spore mosaics indicated that the rodlet fibrillar image is the result of individual particulates, rather than evaginations in a continuous sheet of material. A model of the mature sport envelope was developed from freeze-etch-replicated, thin-sectioned, and critical point dried S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…This above suggests that SapA varies tremendously across the Actinomycetales and may represent niche specificity, of which we know little in the Streptomycetes. These results also correlate well with the high level of detected variation in the presence of rdlA and rdlB, which form the highly insoluble hydrophobic rodlet outer layer of the spores (Wildermuth et al 1971;Smucker and Pfister 1978;Claessen et al 2002) and such variability is supported by the genome sequence of S. avermitilis, where no rdlA/rdlB homologues can be detected and of S. griseus, where the rdl gene cluster is different from that in S. coelicolor. If the ecology of sporoactinomyces varies greatly from terrestrial to aquatic environments, then so will the need for hydrophobic surface proteins, especially when it is known that rodlets are not essential for spore formation (Claessen et al 2002).…”
Section: Resultssupporting
confidence: 73%
“…This above suggests that SapA varies tremendously across the Actinomycetales and may represent niche specificity, of which we know little in the Streptomycetes. These results also correlate well with the high level of detected variation in the presence of rdlA and rdlB, which form the highly insoluble hydrophobic rodlet outer layer of the spores (Wildermuth et al 1971;Smucker and Pfister 1978;Claessen et al 2002) and such variability is supported by the genome sequence of S. avermitilis, where no rdlA/rdlB homologues can be detected and of S. griseus, where the rdl gene cluster is different from that in S. coelicolor. If the ecology of sporoactinomyces varies greatly from terrestrial to aquatic environments, then so will the need for hydrophobic surface proteins, especially when it is known that rodlets are not essential for spore formation (Claessen et al 2002).…”
Section: Resultssupporting
confidence: 73%
“…grown in the presence of a rapidly utilized carbon source such as glucose, including Streptomyces venexuelae (Ahmed et al, 1984), Streptomyces alboniger (Surowitz & Pfister, 1985), Streptomyces peucetius (Dekleva & Strohl, 1987) and Streptomyces lividans (Madden et al, 1996). These authors have reported various patterns of acid production.…”
Section: Discussionmentioning
confidence: 99%
“…One surface layer, called the rodlet layer, has a typical ultrastructure of a mosaic of 8‐ to 10‐nm‐wide parallel rods (Wildermuth et al. , 1971; Smucker and Pfister, 1978). The nature of the surface layers is not known.…”
Section: Introductionmentioning
confidence: 99%